Spaces of comparative literary study When Izz al-Din al-Manasra - Dr. Hussein Lafta Hafez; Dr.Abbas Abdel Halim Abbas; Assis .Lect. Nyan Hussein Abdullah (Journal of College of Education, 2024)
The research deals with Ezz El-Din Al-Manassara’s efforts in theoretical criticism to define concepts in the field of cultural criticism, starting with the historical definition of the emergence of this criticism in the Arabic language, then its appearance in the West, of course through the constellation of critics published in Europe, and by defining the nature of the concept of this criticism and the magazine, The scope of adapting this concept to the Arab literary efforts that have emerged since the beginning of the twentieth century is represented by the Jordanian and Palestinian critic and academic of Izz al-Din al-Manasra, who is unique in comparative literary studies, as he is a critic specialized in this type of research. At the level of theory and practice, he published a group of important works in this direction, which we will detail later. Al-Manasrah also insists on using the term (comparative criticism) and not (comparative literature), so we must look at his achievement with some difference from the achievement of his predecessors and those of him who are Jordanian comparativists. , who dealt with comparative study as (literary history) or only (a literary phenomenon).
Keywords: literary study, comparative literature, Izz al-Din al-Manasra